Oblivious ‘Sex Traffickers’: Challenging stereotypes and the fairness of US trafficking laws - Horning, Amber; Stalans, Loretta (Anti-Trafficking Review, 2022)
In this paper, we explore third parties who unexpectedly fell within the legal definition of a sex trafficker. The anti-trafficking lobby and media stories frequently portray traffickers as organised, psychopathic, violent, and child kidnappers. We dismantle these depictions by showing the unexpected people who qualify as traffickers. This paper incorporates findings from two studies involving eighty-five third parties in New York City and forty-nine in Chicago. We analyse how teenagers, drivers, and boyfriends qualify as traffickers under US law. We find that two-thirds of them hold inaccurate views about the difference between sex trafficking and facilitating prostitution. Trafficking can be incidental or temporary, and traffickers in these samples were often oblivious to their legal status, potentially resulting in lengthy prison sentences. We conclude by calling for differential sentencing based on traffickers’ age, and awareness campaigns designed to alert third parties of the legal distinctions between pandering and sex trafficking.